Inner Source: Open-Source-Prinzipien im Unternehmen anwenden - Kirsch, Christian; Drost-Fromm, Isabel; Tigges, Johannes; Capraro, Maximilian; Dorner, Michael (iX, 2019)
Wenn Regeln für die unternehmensinterne Softwareentwicklung wie strikte Abschottung der Teams zu Schwierigkeiten führen, können Open-Source-Prinzipien helfen. Diesem „Inner Source“-Vorgehen folgen mittlerweile einige große Unternehmen. <br
Keywords: inner source; opensource

Measuring Patch-Flow at Google - Dorner, Michael (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
In the industrial domain, software development is a highly collaborative work involving different contributing teams. But there is not yet a way to quantify the collaboration between organizational units within a software developing company. However, information about this collaboration is latent in software repositories and has not been defined yet. We mined Google’s internal software repository and identified all commits which are assigned to projects of organizational units the patch author does not belong to. We call this phenomena of collaboration beyond organizational borders patch-flow. This work introduces a graph-based metric to quantify this patch-flow. We developed a tool that is able to crawl in Google’s repository and collected patches of 2,500 Google developers in the years 2007, 2009, 2011, and 2013. Due to the missing historical information about organizational unit membership of developers, we provided a clustering approach to assign all developers to organizational units. Because the Google internal data has not been released by now, we crawled and analyzed the Chromium project. Using the Chromium data we were able to apply the patch-flow metric and quantify collaboration over organizational unit boundaries, although the used data source is only suitable to a limited extent. The clustering approach has to be validated.

The Patch-Flow Method for Measuring Inner Source Collaboration - Capraro, Maximilian; Dorner, Michael; Riehle, Dirk (MSR’18: 15th International Conference on Mining Software Repositories, 2018)
Inner source (IS) is the use of open source software development (SD) practices and the establishment of an open source-like culture within an organization. IS enables and requires developers to collaborate more than traditional SD methods such as plan-driven or agile development. To better understand IS, researchers and practitioners need to measure IS collaboration. However, there is no method yet for doing so. In this paper, we present a method for measuring IS collaboration by measuring the patch-flow within an organization. Patch-flow is the flow of code contributions across organizational boundaries such as project, organizational unit, or profit center boundaries. We evaluate our patch-flow measurement method using case study research with a software developing multi-industry company. By applying the method in the case organization, we evaluate its relevance and viability and discuss its usefulness. We found that about half (47.9%) of all code contributions constitute patch-flow between organizational units, almost all (42.2%) being between organizational units working on different products. Such significant patch-flow indicates high relevance of the patch-flow phenomenon and hence the method presented in this paper. Our patch-flow measurement method is the first of its kind to measure and quantify IS collaboration. It can serve as a base for further quantitative analyses of IS collaboration.<br
Keywords: Inner source; internal open source; inner source measurement; patch-flow; open source; open collaboration; software development collaboration measurement; inner source metrics